2011
DOI: 10.1371/journal.pone.0026899
|View full text |Cite
|
Sign up to set email alerts
|

Fatty-Acid Preference Changes during Development in Drosophila melanogaster

Abstract: Fatty-acids (FAs) are required in the diet of many animals throughout their life. However, the mechanisms involved in the perception of and preferences for dietary saturated and unsaturated FAs (SFAs and UFAs, respectively) remain poorly explored, especially in insects. Using the model species Drosophila melanogaster, we measured the responses of wild-type larvae and adults to pure SFAs (14, 16, and 18 carbons) and UFAs (C18 with 1, 2, or 3 double-bonds). Individual and group behavioral tests revealed differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 60 publications
(66 reference statements)
1
28
0
Order By: Relevance
“…preferences for them. Larva prefer unsaturated fatty acids (UFAs), while the adults prefer saturated fatty acids (SFAs) [49]. FA are also sensed by the GRNs on the labellum.…”
Section: The Molecular Basis For Water Co2 and Fatty Acid Taste In Dmentioning
confidence: 99%
“…preferences for them. Larva prefer unsaturated fatty acids (UFAs), while the adults prefer saturated fatty acids (SFAs) [49]. FA are also sensed by the GRNs on the labellum.…”
Section: The Molecular Basis For Water Co2 and Fatty Acid Taste In Dmentioning
confidence: 99%
“…Physiologically, there appears to be no requirement for 20-carbon PUFAs in D. melanogaster , as flies raised in the absence of 20-carbon PUFAs are healthy and fertile (Shen et al, 2010; Hammad et al, 2011). Interestingly, D. melanogaster larvae have a preference for food enriched in unsaturated fatty acids whereas adults display a preference for saturated fatty acids (Fougeron et al, 2011). Although the reason underlying the stage-specific preferences for fatty acids is yet unknown, this differential preference may reflect the varying nutritional requirements during development (Shen et al, 2010; Hammad et al, 2011).…”
Section: Fatty Acid Signaling In Drosophilamentioning
confidence: 99%
“…It has been reported that insects can discriminate long-chain dietary fatty acids. Drosophila melanogaster ( D. melanogaster ) larvae prefer dietary unsaturated fatty acids while the adults generally prefer saturated fatty acids [9]. Low levels of diet fat can enhance the lifespan of the blowfly, while high-fat diets can cause more rapid death [10].…”
Section: Introductionmentioning
confidence: 99%